ANALISIS KECELAKAAN LALU LINTAS JALAN WAY RATAI KABUPATEN PESAWARAN MENGGUNAKAN METODE EAN DAN UCL - Hikmah, Nuril; Ofrial, Siti Anugrah M. Putri; Sulistyorini, Rahayu; Herianto, Dwi (JMTS: Jurnal Mitra Teknik Sipil, 2026)
The Way Ratai Highway serves as a primary transportation corridor connecting Bandar Lampung City to major tourist destinations in Pesawaran Regency, including Mutun Beach, Klara Beach, and Wan Abdul Rachman Grand Forest Park. This 58.8-kilometer route crosses four sub-districts and plays a vital role in supporting tourism-related traffic. The increasing volume of visitors has contributed to a heightened risk of traffic accidents along the corridor. This study aims to examine the characteristics of traffic accidents and to identify accident-prone segments (black sites) using the Equivalent Accident Number (EAN) and Upper Control Limit (UCL) methods. Traffic accident data were obtained from the Traffic Accident Unit of the Pesawaran Police Department, covering the period from 2019 to 2023. The analysis reveals that motorcycles were the most frequently involved vehicles, with the majority of victims being male and under the age of 18. The most common type of accidents was front-side collisions, and the highest frequency of incidents occurred in the afternoon. Based on the EAN and UCL calculations, two segments were identified as black sites: Sukajaya Lempasing Village and Wates Way Ratai Village. These findings are expected to serve as a reference for improving traffic safety along this tourism corridor. Abstrak Jalan Raya Way Ratai merupakan koridor utama penghubung Kota Bandar Lampung dengan destinasi wisata unggulan di Kabupaten Pesawaran, seperti Pantai Mutun, Pantai Klara, dan Tahura Wan Abdul Rachman. Jalan sepanjang 58,8 km ini melintasi empat kecamatan dan menjadi jalur vital bagi wisatawan. Meningkatnya arus wisatawan berdampak pada tingginya risiko kecelakaan lalu lintas di sepanjang ruas ini. Penelitian ini bertujuan untuk menganalisis karakteristik kecelakaan lalu lintas dan mengidentifikasi daerah rawan kecelakaan (blacksite) dengan menggunakan metode Equivalent Accident Number (EAN) dan Upper Control Limit (UCL). Data yang digunakan merupakan data kecelakaan tahun 2019–2023 dari Unit Laka Lantas Polres Pesawaran. Hasil analisis karakteristik kecelakaan lalu lintas menunjukkan bahwa kecelakaan paling banyak melibatkan sepeda motor, dengan korban didominasi laki-laki dan kelompok usia di bawah 18 tahun. Jenis kecelakaan yang dominan adalah tabrakan depan-samping, dan waktu kejadian terbanyak berada pada siang hingga sore hari. Berdasarkan hasil perhitungan EAN dan UCL, dua segmen jalan diidentifikasi sebagai daerah rawan kecelakaan (blacksite), yaitu Desa Sukajaya Lempasing dan Desa Wates Way Ratai. Temuan ini diharapkan menjadi dasar rekomendasi penanganan keselamatan lalu lintas di koridor pariwisata.